2013
DOI: 10.2147/ott.s53876
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the role of p53 splice variants in human malignancy: a clinical perspective

Abstract: Thirty-five years of research on p53 gave rise to more than 68,000 articles and reviews, but did not allow the uncovering of all the mysteries that this major tumor suppressor holds. How p53 handles the different signals to decide the appropriate cell fate in response to a stress and its implication in tumorigenesis and cancer progression remains unclear. Nevertheless, the uncovering of p53 isoforms has opened new perspectives in the cancer research field. Indeed, the human TP53 gene encodes not only one but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
140
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(153 citation statements)
references
References 103 publications
(131 reference statements)
1
140
0
1
Order By: Relevance
“…The Δ40p53 isoforms (also named N-terminally truncated p53 protein (p53/47), or ΔNp53) are generated by alternative splicing of intron 2 and/or alternative initiation of translation [165]. Since these isoforms lack the first 39 amino acids, they do not have TAD1, but retain TAD2.…”
Section: Inducible/modified Proteoforms Of P53mentioning
confidence: 99%
See 3 more Smart Citations
“…The Δ40p53 isoforms (also named N-terminally truncated p53 protein (p53/47), or ΔNp53) are generated by alternative splicing of intron 2 and/or alternative initiation of translation [165]. Since these isoforms lack the first 39 amino acids, they do not have TAD1, but retain TAD2.…”
Section: Inducible/modified Proteoforms Of P53mentioning
confidence: 99%
“…Finally, the Δ160p53α, Δ160p53β, and Δ160p53γ isoforms are characterized by a lack of the first 159 amino acids [165]. Although the currently available information about these p53 variants is very limited, it was found that this group of p53 isoforms was expressed in K562 cells, which were originally considered “p53-null” cells [171,172].…”
Section: Inducible/modified Proteoforms Of P53mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a multidisciplinary team at Yale University, led by Yale Cancer Center members, has confirmed that NF1 is a “major player” in the development of skin cancer [47], which is also observed in this study. The TP53 gene responds to diverse cellular stress to regulate target genes that induce cell cycle arrest, apoptosis, senescence, DNA repair, and/or changes in metabolism [48]. Mutations in TP53 may result in adrenal cortical carcinoma [49], breast cancer [50], choroid plexus papilloma [51], colorectal cancer [52], hepatocellular carcinoma [53], Li-Fraumeni syndrome [54], nasopharyngeal carcinoma [55], osteosarcoma [56], pancreatic cancer [57], basal cell carcinoma [58], and glioma susceptibility [59].…”
Section: Resultsmentioning
confidence: 99%